ENZYME ACTIVITY OF PLEUROTUS OSTREATUS ON REACTIVE BLUE 4 AND REACTIVE BLACK 5 REMOVAL USING SEQUENCE BATCH REACTOR - Christine Sara N., Arthania
The existence of synthetic dyes in the waters affects the quality of life of aquatic flora by affecting the oxygen level in the water. Synthetic dyes of azo and anthraquinone groups contain aromatic structures, so they are not easy to process. White weathered mushrooms do not require environmental preconditions to survive, so they can still produce extracellular enzymes that function as catalysts for processing synthetic dyes waste. The enzymes involved in this processing are the enzyme lacase and lignin peroxidase. Lignin Persoxidase (LiP) can directly oxidize phenolic and non-phenolic compounds, while lacase enzymes can only oxidize phenolic compounds, but with the addition of this enzyme substrate can oxidize non-phenolic compounds. Pleurotus ostreatus mushroom isolate is a type of white rot fungus that was used in this study, and released linolytic enzymes. The treatment of synthetic dye waste uses a sequence batch reactor with variations in the addition of coarse enzymes. The processing of synthetic dye waste without the addition of crude enzymes utilizes enzymes produced from the growth of the fungus Pleurotus ostreatus isolates on bioball inert media. The growth of P. ostreatus fungi isolate on the eleventh day resulted in a degradation of 23.60% for Reactive Blue 4 (RB4) dye waste and 13.57% for Reactive Black 5 (RB5). The addition of the crude enzyme Pleurotus ostreatus resulted in a better level of synthetic color processing, namely 63.58% for RB4 color waste and 19.72% for RB5, with lacase enzyme activity found in RB4 waste treatment, which was 36.68 U / L , and 23.07 U / L at RB5.